Management accounting for decision makers - Atrill, Peter (Pearson, 2021)
"In this edition, we have taken the opportunity to improve the book. We have expanded on the changing role of management accountants to enable them to retain their place at the centre of the decision-making and planning process. In Chapter 1, we have included the recently developed statement of Global Management Accounting Principles. These principles have been identified (by the leading management accounting professional bodies in the UK and US) as those to be followed when determining the information that managers need. In Chapter 7, we have brought in a discussion of current thinking and practice in the area of management control. Throughout this new edition, we have included additional, and more up-to-date, examples of management accounting in practice. We have also added more in-chapter questions and diagrams".